Improved hydrogen storage performances of nanocrystalline RE5Mg41-type alloy synthesized by ball milling. (February 2022) - Yuan, Zeming; Li, Xiaoming; Li, Tao; Zhai, Tingting; Lin, Yonghua; Feng, Dianchen; Zhang, Yanghuan
Highlights: Higher surface activity nanocrystalline Sm5 Mg41 alloy was prepared by milling. Nanocrystalline content rises firstly and then reduces with milling time ascending. Nano boundaries introduced by milling improve hydrogen storage kinetics. Milling for 10 h can reduce E a(de) from ∼128.2 to ∼112.9 kJ/mol. Abstract: In this work, Sm5 Mg41 fabricated by vacuum induction melting was milled to greatly improve the hydrogen storage performances. The alloy has higher surface activity and better hydrogen absorption and desorption properties due to the abundant of crystal defects causing by ball milling. Prolonging the time of milling generates the gradual evolution of microstructure of Sm5 Mg41 alloy from polycrystalline to nanocrystalline as well as amorphous phase. The phase content of nanocrystalline rises firstly and then reduces with the milling time ascending. When milling for 10 h, the milled alloy consists mainly of nanocrystalline phase with many sub-grain boundaries and a small amount of amorphous below 2 nm. Further extending the milling time causes to the reducing of nanocrystalline phase content and the increasing of amorphous phase content. When the ball milling time was 5, 10, 20 and 30 h, the activation energies of dehydrogenation for the Sm5 Mg41 ball milled alloy are 128.2, 112.9, 125.9, and 126.9 kJ/mol H2, respectively, suggesting that ball milling can change the energy barrier of dehydrogenation reaction. The nanocrystalline grain boundaries introduced by milling provide more channels for hydrogen diffusion, thereby enhancing the hydrogen storage kinetics of the as-milled Sm5 Mg41 alloy. The hydrogenation enthalpy changes (Δ H ab ) were -82.387, -77.516, -79.001, and -80.076 kJ/mol H2, respectively. It is suggested that the thermodynamic stability of the as-milled Sm5 Mg41 alloy is weakly reduced by ball milling. The Sm5 Mg41 alloy milled for 10 h has the best hydrogen storage property. It can reversible absorb/desorb hydrogen 4.9 wt.% within 0.5 h at 300 °C.